2021
DOI: 10.1007/s10763-021-10226-6
|View full text |Cite
|
Sign up to set email alerts
|

High School and Preservice Chemistry Teacher Education Students’ Understanding of Voltaic and Electrolytic Cell Concepts: Evidence of Consistent Learning Difficulties Across Years

Abstract: High school students learn the basic voltaic and electrolytic cell concepts during their last year prior to entering an undergraduate teacher-education science degree. During the four years of university, students complete a sequence of topics designed to build on conceptual understanding presented in previous years. At the end of their degrees, graduating students are expected to have developed a comprehensive understanding of the subject that they are required to teach. In this research, we designed and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
2
6
0
1
Order By: Relevance
“…Although more than half of the students from both countries answered the question 17 correctly, it was concluded that approximately 40% of the students could not distinguish the minus and plus poles of an electrolytic cell by looking at the electrochemical reactions. This conclusion is also in line with the result of the other studies concerning electrolysis and electrolytic cells (Garnet and Treagust, 1992b;Sia et al, 2012;Rahayu et al, 2022). In this case, the problem seems to be with students did not concentrate on the electron transfer at the electrodes while determining the charge of the cell pole.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although more than half of the students from both countries answered the question 17 correctly, it was concluded that approximately 40% of the students could not distinguish the minus and plus poles of an electrolytic cell by looking at the electrochemical reactions. This conclusion is also in line with the result of the other studies concerning electrolysis and electrolytic cells (Garnet and Treagust, 1992b;Sia et al, 2012;Rahayu et al, 2022). In this case, the problem seems to be with students did not concentrate on the electron transfer at the electrodes while determining the charge of the cell pole.…”
Section: Discussionsupporting
confidence: 86%
“…Both the Indonesian and Turkish SHS students' overall understanding of the concepts in electrochemistry was weak and they had major difficulties concerning electrochemical concepts and topics. This result is in line with the results of the studies conducted by students from many countries, that electrochemistry subjects and concepts are difficult for students (Allsop and George, 1982;Barral et al, 1992;Treagust, 1992a, 1992b;Ogude and Bradley, 1994;Sanger and Greenbowe, 1997a;Ahtee et al, 2002;Lin et al, 2002;O ¨zkaya 2002;Schmidt et al, 2007;Rahayu et al, 2011;Akram et al, 2014;Supasorn, 2015;Loh and Subramaniam, 2018;Nakibog ˘lu, 2018a, 2018b;Rahayu et al, 2022). Although the countries compared here have two different geographical regions and cultures, such as Indonesia, an Asian country, and Tu ¨rkiye, which is located in both Asia and Europe, there was no significant difference between the average scores achieved.…”
Section: Discussionsupporting
confidence: 86%
“…The studies have shown that electrochemistry concepts are perceived as challenging by students and that both secondary school and university chemistry students have misconceptions of the concepts of electrochemistry (Allsop & George, 1982;Brandriet & Bretz, 2014;De Jong &Treagust, 2003;Treagust, 1992a and1992b;Lu & Bi, 2016;Nakiboğlu, 2017a and2017b;Nakiboğu & Nakiboğlu, 2018, Ogude & Bradley, 1994Özkaya, 2002;Rahayu et al, 2011;Rahayu et al, 2021;Serger &Greenbowe, 1997a and1997b). The problem underlying the learning difficulties concerning the concepts of electrochemistry includes all the issues addressed at the beginning of the introduction concerning chemistry learning difficulties in general.…”
Section: The Rationale and Research Questions Of The Studymentioning
confidence: 99%
“…Studies have shown that all level students have problems understanding chemistry topics and concepts (Nakhleh, 1992;Nakiboğlu, 2003;Nakiboğlu, 2006;Nakiboğlu and Nakiboğlu, 2019;Nyachwaya et al, 2011;Rahayu, Treagust and Chandrasegaran, 2021;Sanger and Greenbowe, 1997;Taber, 1994;Taber et all., 2012). The students can also have misconceptions about many chemistry concepts because chemistry concepts seem too abstract for students at this level.…”
Section: Introductionmentioning
confidence: 99%